Association of the GNAS locus with severe malaria. Human Genetics, - Auburn, S.; Diakite, M.; Fry, A.E.; Ghansah, A.; Campino, S.; Richardson, A.; Jallow, M.; Sisay-Joof, F.; Pinder, M.; Griffiths, M.J.; Peshu, N.; William, T.N.; et al. (My University, 2008)
Functional studies have demonstrated an interaction between the stimulatory G protein alpha subunit (G-alpha-s) and the malaria parasite at a cellular level. Obstruction of signal transduction via the erythrocyte G-alpha-s subunit reduced invasion by Plasmodium falciparum parasites. We sought to determine whether this signal pathway had an impact at the disease level by testing polymorphisms in the gene encoding G-alpha-s (GNAS) for association with severe malaria in a large multi-centre study encompassing family and case - control studies from The Gambia, Kenya and Malawi, and a case - control study from Ghana. We gained power to detect association using meta-analysis across the seven studies, with an overall sample size approximating 4,000 cases and 4,000 controls. Out of 12 SNPs investigated in the 19 kb GNAS region, four presented signals of association (P < 0.05) with severe malaria. The strongest single-locus association demonstrated an odds ratio of 1.13 (1.05-1.21), P = 0.001. Three of the loci presenting significant associations were clustered at the 5-prime end of the GNAS gene. Accordingly, haplotypes constructed from these loci demonstrated significant associations with severe malaria [OR = 0.88 (0.81-0.96), P = 0.005 and OR = 1.12 (1.03-1.20), P = 0.005]. The evidence presented here indicates that the influence of G-alpha-s on erythrocyte invasion efficacy may, indeed, alter individual susceptibility to disease. © Springer-Verlag 2008.
Keywords: EMTREE drug terms: guanine nucleotide binding protein alpha subunit EMTREE medical terms: article; case control study; clinical trial; disease severity; DNA polymorphism; Gambia; gene locus; genetic association; genetic susceptibility; Ghana; human; Kenya; malaria; malaria falciparum; Malawi; meta analysis; nucleotide sequence; priority journal; protein function; protozoal genetics; single nucleotide polymorphism; systematic review